Traffic and Highway Engineering, Enhanced SI Edition, 5th Edition - Nicholas J. Garber; Lester A. Hoel (Cengage Learning, 2019)
Gain unique insights into all facets of today's traffic and highway engineering with the enhanced edition of Garber and Hoel's best-selling TRAFFIC AND HIGHWAY ENGINEERING, SI Edition, 5th Edition. This edition initially highlights the pivotal role that transportation plays in today's society. Readers examine employment opportunities that transportation creates, its historical impact and the influences of transportation on modern daily life. This comprehensive approach offers an accurate understanding of the field with emphasis on some of transportation's distinctive challenges. Later chapters focus on specific issues facing today's transportation engineers to prepare readers to overcome common obstacles in the field. Worked problems, diagrams and tables, reference materials and meaningful examples clearly demonstrate how to apply and build upon the transportation engineering principles presented. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.